Effects of cross country fiscal interdependence on multipliers within a monetary union - Vanessa Kunzmann (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2022)
This paper analyzes the effects of time-varying fiscal policy behavior on output and consumption multipliers within a monetary union. The framework is that of a standard New Keynesian twocountry model with distortionary taxes and Calvo price rigidities. I first show that multipliers differ significantly across fiscal regime mixes that follow a two-state Markov switching process. For each country, I differentiate between active, where spending is mainly deficit-financed, and passive, when spending is mainly tax-financed, behavior. Since this analysis is based on the Euro Area, I abstract from fiscal-monetary interaction and focus on member and union fiscal interdependence, including monetary imperfections and trade effects. My calibration results show that consumption multipliers to be small and negative. However, the output multiplier is positive and possibly larger than one, depending on the persistence and openness of a country. Moreover, the optimal fiscal regime mix is a combination of active/passive since the negative wealth effect is lowest and the terms of trade loss are the smallest.
Keywords: R0; R11; R14; R21; R31; 330; Fiscal Policy; Fiscal Multiplier; Multiplier; European Monetary Union; Regime Switching; Fiscal Policy Rules